21. 100 Collaborative Products and their Uses - Baggaley, Jon; Depow, Jim; Klaas, Jim; Wark, Norine (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2003)
This report highlights trends that have emerged from the evaluation of 100 online collaborative tools in this series of reports so far (2001-03). Emphasis is placed upon the special requirements of distance education (DE) users of collaborative tools, in the selection of online text/ audio/ video-conferencing, polling and whiteboard methods, and integrated course delivery systems combining all of these features. The technical and didactic skills for using collaborative tools effectively are illustrated in relation to a standard freeware for online audio-conferencing.